(untitled) (Bioagro, 2025)
Cocoa seeds are recalcitrant, resulting in a faster loss of viability with storage time and the tetrazolium test is an alternative to determine the viability of these seeds as quickly as possible. The objective of this study was to develop a tetrazolium test protocol for cocoa seeds to assess seed viability. Seeds were extracted from fruits and after the processing were subjected to the tetrazolium test considering 7 times in tetrazolium solution (2, 3, 4, 5, 6, 7 and 8 hours) and 2 concentrations of tetrazolium solution (0.05 % and 0.075 %). Before this, seeds were soaking for 6 hours in germination paper and the seed coats were removed. During the immersion on tetrazolium solution, seed were maintained in a germination chamber at 42 °C. After this, seeds were categorized into 4 classes, according to the coloration of embryonic axis, with the living tissues being dyed with light pink color while dead tissues were non-colored. To confirm the results of tetrazolium test, a germination test was carried out to associate the percentage of germination with the percentage of viable seeds obtained by the tetrazolium test. Considering this, the recommended immersion time in the tetrazolium solution is 3 hours with a concentration of 0.05 %.